Revitalizing English Teaching: Insights from Diniyah Madrasah Educators - Dewi Masitah; M. Syaikhudin (IJLHE: International Journal of Language, Humanities, and Education, 2024)
The aim of this research is to analyze Firstly, what are the innovations in English language learning for Madrasah Diniyah teachers, especially older ones at STAI Al-Yasini Pasuruan? Second, what is the motivation for learning English for Madrasah Diniyah teachers at STAI Al-Yasini Pasuruan. The relevant theories in analyzing this research are innovation theory and McClelland's Achievement Motivation Theory. The research method is qualitative phenomenology. The results of this research are first, the innovation in English language learning for Madrasah Diniah teachers psychologically has taken into account the elements: 1) freedom from traditional authority and anti-dogmatic thinking, that English can be a wider tool for preaching. 2) paying attention to community problems, meaning combining English words with Arabic letters reduces the problems of Madin teachers who are not used to speaking English 3) open to new experiences or not awkward with English 4) Confident in knowledge and reasoning. 5) Responsive planning, future oriented, not easily satisfied. 6) in English, Madarasah Diniah teachers have high aspirations, are educated, cultured and professional. Second, in McCleland's view, the scholarships provided by the Pasuruan Regency government are a form of attention, cleanliness and extrinsic motivation to Madrasah Diniyah teachers so that they can develop and be in harmony with teachers in schools in general who have degrees. Third, according to McClelland, Pasuruan Madrasah Diniyah teachers have potential that can be developed through individual motivation, and are supported by the situation and opportunities available such as scholarships for Madrasah Diniyah teachers provided by the Pasuruan district government. Potential here according to McClelland refers to three forms of needs, namely; 1) the need for achievement (need of achievement), 2) the need for power (need of power), 3) the need for affiliation (need of affiliation). These three forms of needs have been fulfilled by the students of Madrasah Diniyah teachers.